Popular terminology for "abduction"of girls - Rajković, Marijeta (Array, 2007)
During the 1960-ies, ethnographic material was collected on the territory of former Yugoslavia for the Ethnological Atlas. A theme number 119, presented in this research was entitled Irregular ways of getting married. More precisely, there were three different types of "abduction" ; a real one (against the will of both a girl and her family), arranged abduction a) with the girl's permission, b) with the girl's permission, but without the permission of her family, and finally c) fake abduction - with the permission of both, the girl and the family, but with a violent pretence. A presentation of popular terminology of abduction obtained from 3200 questionnaires of the Ethnological Atlas of Yugoslavia, covering the whole territory of former Yugoslavia is shown in this article.